53.4k views
3 votes
Complete the recursive formula of the arithmetic sequence -3,-1,1,3

User OPK
by
5.9k points

2 Answers

3 votes

Explanation:


- 3 + 11 - 3 = 8

User Steve Mitchell
by
5.4k points
6 votes

Answer:

b(1)=-3

b(n)=b(n−1)+2

Explanation:

Given the sequence −3,−1,1,3,...

We can infer that the first number of the sequence is -3, and the difference is +2

b(1)=first number of the sequence

b(n)=b(n−1) diffrence

If we fill this in, we get:

b(1)=-3

b(n)=b(n−1)+2

User Odedsh
by
4.9k points